Understanding droplet jetting on varying substrate for biological applications - Lee, Jia Min (2023)
In the inkjet printing process, the droplet experience two phases, namely the jetting and the impacting phases. In this review article, we aim to understand the physics of a jetted ink, which begins during the droplet formation process. Following which, we highlight the different impacts during which the droplet lands on varying substrates such as solid, liquid, and less commonly known viscoelastic material. Next, the article states important process-specific considerations in determining the success of inkjet bioprinted constructs. Techniques to reduce cell deformation throughout the inkjet printing process are highlighted. Modifying postimpact events, such as spreading, evaporation, and absorption, improves cell viability of printed droplet. Last, applications that leverage on the advantage of pixelation in inkjet printing technology have been shown for drug screening and cell-material interaction studies. It is noteworthy that inkjet bioprinting technology has been integrated with other processing technologies to improve the structural integrity and biofunctionality of bioprinted construct.